Optimization, kinetic studies, and upscaling of vacuum evaporation for pineapple concentrates - Chua, Lee Suan (American Chemical Society, 2022)
This study was focused on the optimization of concentrating Morris pineapple juice using a rotary vacuum evaporator from 60 to 70 °C for 30-60 min. The vacuum evaporation could reduce 38.3% water, increase sugar to 14.6 °Brix, form negligible 5-(hydroxymethyl)furfural (HMF), 2.91 mg/mL, and retain about one-third of the original proteolytic activity (2822.20 GDU/g) of bromelain in the pineapple concentrate at 60 °C for 60 min. Water removal was found to follow zero-order kinetics, whereas sugar and HMF increment, as well as degradation of bromelain activity, could be described by first-order kinetics. The process was upscaled to a 12-fold increase of the evaporator size and showed about 20% poorer performance in water reduction due to the low ratio of heat transfer surface area to volume. Rotary vacuum evaporation could be a good choice to concentrate Morris pineapple juice because of less HMF formation and >30% bromelain activity retention.